Administrational Factors as Predictors of Teacher Burnout across Iranian and Turkish EFL Teachers - KHEZERLOU, Ebrahim (Journal of History Culture and Art Research, 2013)
The study aimed at measuring the perceived burnout levels of Iranian (N= 230) and Turkish (N=156) EFL teachers and determining the role of four administrational factors (i.e., Teacher Autonomy, Reward Adequacy, Fairness, and Fringe Benefits) in predicting EE, DP and PA burnout processes across Iranian and Turkish EFL teachers. The MBI-ES was used to measure the perceived burnout levels of the participants, and a four-dimension scale (41 items) was developed based on the literature study to measure the participants’ perceptions in these four areas. The average internal consistency reliability of the 41-item scale was r = 0.703. The results of t-tests analyses showed that there was a slight significant difference between Iranian and Turkish groups only in EE burnout processes. Moreover, the results of regression analyses showed that EE, DP, and PA subscales were better predicted by Fairness factor among Iranian teachers, while by Teacher Autonomy among Turkish teachers. Finally, the contrasted results also revealed that Teacher Autonomy, Reward Adequacy, and Fairness factors had cross-culturally discriminatory roles, while Fringe Benefits factor did not have.